1996
DOI: 10.1063/1.471685
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Zn(4s4p 3P1) and Cd(5s5p 3P1) with SiH4

Abstract: Electron states of benzene-Br2 donor-acceptor complex: HeI photoelectron spectroscopy and ab initio molecular orbital study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 72 publications
1
15
1
Order By: Relevance
“…Some of these products are useful in the industry to get hydrogenated amorphous silicon ͑a-Si:H͒ among other applications. Breckenridge et al [24][25][26] studied the reactivity of excited metal atoms with SiH 4 molecules in the gas phase. Electronic mail: hpacheco@ittoluca.edu.mx.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these products are useful in the industry to get hydrogenated amorphous silicon ͑a-Si:H͒ among other applications. Breckenridge et al [24][25][26] studied the reactivity of excited metal atoms with SiH 4 molecules in the gas phase. Electronic mail: hpacheco@ittoluca.edu.mx.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that both Cd(5s5p 3 P 1 ) and Zn(4s4p 3 P 1 ) readily activate Si−H bonds in SiH 4 , forming the metal hydride molecules and SiH 3 in the gas phase. In contrast, these reagents 1,2,4,5,13,15,49-51 [as well as the analogous Hg(6s6p 3 P 0,1 ) states 1,2,4,5 ] are very inefficient in activating the C−H bonds in CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…By using the pump–probe technique, Breckenridge and co-workers have thoroughly investigated the reactions of n s n p metal atoms with H 2 , CH 4 , SiH 4 , and GeH 4 in the gas phase . The experimental and theoretical studies suggest that the reactions of the n s n p ( 1 P) excited-state group II metal atoms with EH 4 (E = C, Si, Ge) molecules favored the side-on insertion mechanism instead of direct abstraction of H from EH 4 by end-on attack of the E–H bond. The reactions of methane with naked metal atoms have been widely studied using the matrix isolation technique. In the low-temperature noble gas matrix, laser-ablated group IIA (Be, Mg, and Ca) and group IIB (Zn, Cd, and Hg) metal atoms react with methane upon photolysis, leading to the formation of HMCH 3 molecules.…”
Section: Introductionmentioning
confidence: 99%